Employment-related mobility, regulatory weakness and potential fatigue-related safety concerns in short-sea seafaring on Canada's Great Lakes and St. Lawrence Seaway: Canadian seafarers' experiences. (January 2020) - Shan, Desai; Neis, Barbara
Highlights: Limited research attention has been paid to fatigue-related issues in the short-sea, domestic segment of seafaring. Canadian short-sea seafarers can suffer from acute and chronic fatigue associated with lack of rest hours, broken watches, the neglect of commute-related fatigue and long rotations. Canadian domestic maritime labour standards for rest hours need to be improved to ensure Canadian seafarers have equivalent minimum hours of rest protection to their international and European counterparts. Abstract: Shipping is a safety-critical industry and seafaring is a demanding job. Fatigue among seafarers is attracting increasing attention due to its implications for their health and safety, for public safety and for environmental risk. Seafaring, like other forms of transportation work entails work on moving (floating) and geographically mobile platforms. Existing studies on seafaring and fatigue have focused mainly on international seafaring and on the relationship between work on mobile work platforms, work-scheduling and fatigue, including its effects on navigation in that sector. Less attention has been paid to fatigue-related issues in the short-sea, domestic segment of seafaring including patterns of extended commuting for work in that sector that may contribute to fatigue and the risk of injury and incidents. This paper reports on findings from a Canadian study of mobility to (commuting) and within work and safety in short-sea shipping on the St. Lawrence Seaway and Great Lakes. This segment of Canadian shipping is associated with high numbers of accidents and incidents. The study comprised 25 in-depth interviews with seafarers, managers from Canadian shipping companies, union representatives and government and other key informants carried out between July 2017 and April 2018. It also included a review of relevant statutes, collective agreements and legal cases. Results from 17 interviews with current and former seafarers and company managers and some of the legal findings are presented here. When asked about safety-related challenges, fatigue was the most commonly identified challenge in these interviews. Eleven out of 17 Canadian, current and ex-seafarers (with the latter now engaged in other roles in the sector) identified fatigue as a challenge. Findings suggest that a combination of (a) extended geographical mobility (commuting) to work, (b) intensive demands and long working hours associated with manoeuvring vessels through the St. Lawrence Seaway and Great Lakes and into and out of ports, (c) the failure to monitor and include commute-related fatigue in calculating eligibility for hours of rest, and (d) lower than international and European Union statutory requirements for hours of rest in Canadian regulations contribute to the risk of fatigue-related accidents and incidents in this work.